ENSURING THE DIGITIZATION OF PUBLIC SERVICES AS A PREREQUISITE FOR THE DEVELOPMENT OF CYBER SPACE IN THE REPUBLIC OF KAZAKHSTAN: THE EXPERIENCE OF FOREIGN COUNTRIES - Useinova G.R.; Ospanova D.A.; Useinova K.R.; Shermukhametova Zh. (Хабаршы. Заң сериясы, 2018)
The urgency of the article is determined by the following factors: the acceleration of digital modern-ization in Kazakhstan under the application of global informatization leads to the transition to electronic document circulation; Increasing the efficiency of the Kazakh government through the introduction of in-formation technology; the task is to accelerate the economic and political modernization of Kazakhstan’s society through the extensive use of information technologies, as well as theoretical and practical interest in studying the potential benefits of e-government and electronic document management.